PENINGKATAN KEMAMPUAN MANAJERIAL PETANI MELALUI PELATIHAN MANAJEMEN PENCATATAN USAHATANI DI KABUPATEN WONOGIRI - Suswadi, Suswadi; Mahananto, Mahananto; Arum, Mutiarra Ridyo; Arbianti, Arbianti; Yuniastuti, Faustina; Aryani, Alina Dian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2025)
The success of the farming system supports the development of Indonesian agribusiness. One of the determinants of the success of farming is the managerial ability of farmers in making decisions. The managerial ability of farmers is shown by one of the abilities in carrying out farming records. However, based on the conditions in the field, it shows that the majority of farmers do not have the knowledge and ability. The purpose of this community service activity is to carry out farm recording training to improve the managerial ability. This community service activity was carried out in Gudangharjo Village, Paranggupito District. Participants in this activity were representatives of farmer groups with a total of 25 participants. The activity began with a pre-test, then socialization and training, and ended with an evaluation through a post-test. The results of this community service activity have proven to be able to improve the managerial ability of farmers. This can be seen from the results of the evaluation related to farmers' awareness of the function of recording farming businesses by (87%) and farmers' willingness to implement recording as an important (74%). Furthermore, the farmers have increased understanding after participating in the training, as indicated by an increase in indicators related to the importance of recording costs in farming (68%), increased knowledge in distinguishing between fixed and variable costs (58%), and understanding the ability to read farming records (45%). So that the results of the farming recording training can help improve the managerial abilities of farmers.